Neuropharmacological properties of Mikania scandens (L.) Willd. (Asteraceae) - Protapaditya Dey; Sangita Chandra; Priyanka Chatterjee; Sanjib Bhattacharya (Wolters Kluwer Medknow Publications, 2011)
Mikania scandens (L.) Willd. (Asteraceae), known as climbing hemp weed in English, is a herbaceous climbing vine grown as a weed throughout the plains of the Indian subcontinent. The present study evaluated some neuropharmacological properties of hydroalcoholic extract of aerial parts from M. scandens (HAMS) in experimental animal models. HAMS (at 250 and 500 mg/kg body weight, i.p.) was evaluated for central antinociceptive activity by tail flick method. Locomotor depressant activity was measured by means of an actophotometer. Skeletal muscle relaxant effect was evaluated by using rotarod apparatus and sedative potentiating property by phenobarbitone-induced sleep potentiation study. The results of the present study revealed significant (P<0.001) and dose-dependent central antinociceptive, locomotor depressant, muscle relaxant, and sedative potentiating effects of HAMS, demonstrating its depressant action on the central nervous system (CNS). From the present study, it can be concluded that the aerial parts of M. scandens possessed prominent depressant action on the CNS, as manifested by the important neuropharmacological properties in mice.